Bear Gulch style shield heraldry: Iconography of a Protohistoric period Northwestern Plains Warrior Society. (May 2014) - Keyser, James D.; Kaiser, David A.
Abstract : The Bear Gulch and Atherton Canyon rock art sites in central Montana contain images of 1024 shield-bearing warriors and an additional 150 freestanding shields. More than 800 of these shields are decorated with heraldic designs characteristic of the Bear Gulch style, and form the largest corpus of Plains decorated shields. Using the system of basic meaningful units, Bear Gulch style designs can be grouped into five geometric and five representational categories, but a count of individual shields shows that the heraldic system was overwhelmingly based on geometric division of the shield's circular face. The various design categories are described and interpreted and the entire corpus of Bear Gulch style shields is compared with Castle Gardens rock art style shields and shields from Historic period Cheyenne culture.